2016
DOI: 10.1039/c6ob00928j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of misfolded glycoprotein dimers through native chemical ligation of a dimeric peptide thioester

Abstract: Glycoprotein quality control processes are very important for an efficient production of glycoproteins and for avoiding the accumulation of unwanted toxic species in cells. These complex processes consist of multiple enzymes and chaperones such as UGGT, calnexin/calreticulin, and glucosidase II. We designed and synthesized monomeric and dimeric misfolded glycoprotein probes. Synthetic homogeneous monomeric glycoproteins proved to be useful substrates for kinetic analyses of the folding sensor enzyme UGGT. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Having concluded that UGGT's promiscuity is not dependent on the flexible linker between the catalytic domain and the N-terminal misfold sensing region, but is likely underpinned by the motions uncovered by the MD simulations, the question remains regarding UGGT's reported ability to survey not only folding of small-and medium-size glycoprotein monomers, but also quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes [23] [24] [25]. The Indeed, the MD conformational landscape observed in this work reaches extremely compact conformations, which may explain the activity of the enzyme against synthetic glycopeptides [16][17][18][19][20]. Importantly, monomeric UGGT can recognize and re-glucosylate a misfolded glycoprotein only if it can bridge the distance between a folding defect and at least one of the glycoprotein's N-linked glycosylation sites.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Having concluded that UGGT's promiscuity is not dependent on the flexible linker between the catalytic domain and the N-terminal misfold sensing region, but is likely underpinned by the motions uncovered by the MD simulations, the question remains regarding UGGT's reported ability to survey not only folding of small-and medium-size glycoprotein monomers, but also quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes [23] [24] [25]. The Indeed, the MD conformational landscape observed in this work reaches extremely compact conformations, which may explain the activity of the enzyme against synthetic glycopeptides [16][17][18][19][20]. Importantly, monomeric UGGT can recognize and re-glucosylate a misfolded glycoprotein only if it can bridge the distance between a folding defect and at least one of the glycoprotein's N-linked glycosylation sites.…”
Section: Discussionmentioning
confidence: 94%
“…Since the discovery of UGGT back in 1989 [11,12], activity studies have used a range of glycoprotein substrates, such as urea-misfolded bovine thyroglobulin [11], mutants of exo-(1,3)-β-glucanase [13], RNase BS [14,15], small size synthetic compounds bearing high-mannose glycans attached to fluorescent aglycon moieties such as 'TAMRA' and 'BODIPY' [16,17] and chemically synthesized misfolded glycoproteins [18][19][20], to mention only a few. Although a comprehensive list of physiological UGGT substrate glycoproteins has not been compiled, and the molecular detail on UGGT:substrate interactions remains uncharacterized, it is apparent that the enzyme is highly promiscuous.…”
Section: Discussionmentioning
confidence: 99%
“…The Totani and Ito group reported that G1M9-glycan still interacts with UGGT after UGGT inspection/glucosylation and proved that the addition of CRT accelerates the dissociation of the G1M9-glycan and UGGT complex. 35 The reported K m value of UGGT for misfolded M9-glycoprotein and CNX/CRT for G1M9-glycoprotein was in the submicro− micromolar range, 14,36,37 while glucosidase-II shows a larger K m value. 38 On the basis of these kinetic results, the GQC cycle appears to be an ordered cycle consisting of UGGT, CNX/CRT-ERp57, and then glucosidase-II.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…Since the discovery of UGGT in 1989 (Parodi, 2007;Trombetta et al, 1989), UGGT activity studies have used a range of glycoprotein substrates (Trombetta et al, 1989;Taylor et al, 2004;Ritter and Helenius, 2000;Ritter et al, 2005), small-size glycosylated synthetic compounds (Totani et al, 2006(Totani et al, , 2009, and chemically synthesized misfolded glycoproteins (Izumi et al, 2016a(Izumi et al, , 2016bKiuchi et al, 2018). In addition to glycoprotein monomers, UGGT also surveys the quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes (Keith et al, 2005;Zhang et al, 2011;Gardner and Kearse, 1999).…”
Section: Discussionmentioning
confidence: 99%